(untitled) (Medico Legal Update, 2020)
Objectives: To assess knowledge and practices related to the prevention of iron deficiency anemia among pregnant women and to find an association between their knowledge; practices and socio-demographic variables. Methodology: This is an institutional descriptive study conducted on the random selection of six primary healthcare centers in Al-Amara city. A purposive sampling technique was used to select (280) pregnant mothers attending antenatal care service. Results: Almost half of the sample belongs to the primary education level (50.3%) and most of them housewife (56.8%), with low monthly income (71.8%). Over three quarters of the sample had moderate knowledge (76.1%) and their unfavorable practices (75.5%) with regard to iron anemia. The results indicated a high relationship between the knowledge and practice of women with the variables under study (p= 0.000). Conclusion: The study concluded that the majority of participants have insufficient knowledge with moderate practices towards preventing this type of anemia. Health education about foods with a high concentration of iron is an essential step towards reducing iron deficiency anemia in pregnant women.